Musical Performance - Lovrenčič , Tea (Širjenje obzorij o poučevanju glasbe, 2025)
This section focuses specifically on musical performance, a term situated within the broader context of musical activities such as listening, performing, and creating. The discussion centers on how pupils perform music and how this is encouraged in the classroom. Emphasis is placed on the role of musical play as an approach to stimulate musical activity and enhance students' social skills. The importance of mistakes and the learning process they foster in musical performance is also addressed. Additionally, the integration of ICT in teaching musical arts is highlighted, alongside the significance of collaboration among various stakeholders—students, teachers, parents, and schools—in public performance and participation in events. This collaboration promotes students' self-confidence and strengthens their self-esteem.